Ang dalawang haring siga - Villanueva, Rene O. (UNICEF, 2015)
"Once upon a time, there lived two macho kings who did nothing but fight because they were annoyed with each other. The two king chose to go to war instead of discussing their problems with one another."--Page 4 of cover.